Spinoza on Envy and the Problem of Intolerance - Green, Keith (Roczniki Filozoficzne, 2024)
In this paper, I examine Spinoza’s account of envy (invidia) with specific attention to his consistent remarks about envy in the context of “superstition”—how “superstition” amplifies envy as an affect, that along with fear and ambition, motivates intolerance. Spinoza counterposes his methodological commitment to view the affects, on a “geometric” model, to Aristotelian and scholastic accounts, and to Descartes’ Passions of the Soul. But they inform his account of the relationship between envy, esteem (gloria), pride (superbia), self-depreciation (abjection), and ambition (ambitio). Spinoza argues that that envy just is a form of hate, it encompasses both sadness at another’s good, but joy at others’ misfortune, and he regards it as evil, even though he refuses to describe it as a vice. Within his methodological framework, it is a consciousness of weakness with an idea of others’ good as the cause. This accounts for its amplification by “superstition”, and its role in motivating ambition and intolerance. I focus, in particular, on the implications of Spinoza’s discussion for tolerance of moral disagreement and difference.